2015
DOI: 10.4067/s0717-95022015000400002
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis of Major Segments of Coronary Artery Occlusion: Importance in Myocardial Revascularization Surgery

Abstract: SUMMARY:Revascularization surgery should ensure morphological similarity between the coronary artery and the graft. This is an important factor for its duration and permeability. The aim of this study was to analyze the morphological characteristics and morphometrics of the coronary artery segments with greater occlusion. This was an observational, cross-sectional descriptive study that consisted of two phases. A macroscopic phase in which 11 cadaveric hearts were extracted and coronary dominance and length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…[13][14][15][16] There is insufficient evidence evaluating the specific segments of the coronary arteries where atheromas are most often located, or their size. It is reported that most atheromas occupy the proximal segments, 13,17) and these are usually the largest. 17) This is most likely because these segments have a greater luminal diameter.…”
Section: Coronary Arteriesmentioning
confidence: 99%
See 4 more Smart Citations
“…[13][14][15][16] There is insufficient evidence evaluating the specific segments of the coronary arteries where atheromas are most often located, or their size. It is reported that most atheromas occupy the proximal segments, 13,17) and these are usually the largest. 17) This is most likely because these segments have a greater luminal diameter.…”
Section: Coronary Arteriesmentioning
confidence: 99%
“…It is reported that most atheromas occupy the proximal segments, 13,17) and these are usually the largest. 17) This is most likely because these segments have a greater luminal diameter. Atheromas' size is important because the severity of coronary artery disease is one of the factors that determine the graft selection for CABG.…”
Section: Coronary Arteriesmentioning
confidence: 99%
See 3 more Smart Citations